Interstitial Lung Disease in Connective Tissue Disease: A Common Lesion With Heterogeneous Mechanisms and Treatment Considerations - Shao, Tihong; Shi, Xiaodong; Yang, Shanpeng; Zhang, Wei; Li, Xiaohu; Shu, Jingwei; Alqalyoobi, Shehabaldin; Zeki, Amir A.; Leung, Patrick S.; Shuai, Zongwen (Frontiers in Immunology, 2021)
Connective tissue disease (CTD) related interstitial lung disease (CTD-ILD) is one of the leading causes of morbidity and mortality of CTD. Clinically, CTD-ILD is highly heterogenous and involves rheumatic immunity and multiple manifestations of respiratory complications affecting the airways, vessels, lung parenchyma, pleura, and respiratory muscles. The major pathological features of CTD are chronic inflammation of blood vessels and connective tissues, which can affect any organ leading to multi-system damage. The human lung is particularly vulnerable to such damage because anatomically it is abundant with collagen and blood vessels. The complex etiology of CTD-ILD includes genetic risks, epigenetic changes, and dysregulated immunity, which interact leading to disease under various ill-defined environmental triggers. CTD-ILD exhibits a broad spectra of clinical manifestations: from asymptomatic to severe dyspnea; from single-organ respiratory system involvement to multi-organ involvement. The disease course is also featured by remissions and relapses. It can range from stability or slow progression over several years to rapid deterioration. It can also present clinically as highly progressive from the initial onset of disease. Currently, the diagnosis of CTD-ILD is primarily based on distinct pathology subtype(s), imaging, as well as related CTD and autoantibodies profiles. Meticulous comprehensive clinical and laboratory assessment to improve the diagnostic process and management strategies are much needed. In this review, we focus on examining the pathogenesis of CTD-ILD with respect to genetics, environmental factors, and immunological factors. We also discuss the current state of knowledge and elaborate on the clinical characteristics of CTD-ILD, distinct pathohistological subtypes, imaging features, and related autoantibodies. Furthermore, we comment on the identification of high-risk patients and address how to stratify patients for precision medicine management approaches.